Peningkatan Kompetensi Guru di SMK Muhammadiyah 2 Malang melalui Pelatihan Pengembangan Media Pembelajaran Berbasis Kecerdasan Buatan - Faiq Madani; Ahmad Ilham; Muhammad Sam’an; Rima Dias Ramadhani; Akhmad Fathurrohman; Safuan Safuan; Muhammad Munsarif; Lukman Assaffat; Wendy Sarasjati; Dhendra Marutho (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to evaluate the effectiveness of the Artificial Intelligence-Based Learning Media Development Program (P3MP-AI) in enhancing teachers’ technological and pedagogical competencies at SMK Muhammadiyah 2 Malang. The program employed a descriptive approach using both quantitative and qualitative methods, including pre-test and post-test assessments, as well as direct observation of the training process. A total of 30 teachers from various disciplines actively participated in the program conducted on August 12, 2025. The evaluation results revealed an increase in the participants’ average scores from 100 to 130 out of a maximum of 150, indicating a significant improvement in their understanding of AI concepts and applications in education. Beyond competency enhancement, the training also fostered teachers’ confidence, creativity, and ability to integrate AI-based tools into interactive learning media. However, several challenges were identified, such as limited technological resources and time constraints in classroom implementation. Overall, this program has made a tangible contribution to strengthening teachers’ digital literacy and can serve as a replicable professional development model for other vocational schools seeking to advance AI-based educational transformation.